A novel lncRNA ARST represses glioma progression by inhibiting ALDOA-mediated actin cytoskeleton integrity - Jun Sun; Dong He; Yibing Fu; Rui Zhang; Hua Guo; Zhaojuan Wang; Yanan Wang; Taihong Gao; Yanbang Wei; Yuji Guo; Qi Pang; Qian Liu (2021)
Glioma is one of the most aggressive malignant brain tumors that is characterized with inevitably infiltrative growth and poor prognosis. ARST is a novel lncRNA whose expression level is significantly decreased in the patients with glioblastoma multiforme. However, the exact mechanisms of ARST in gliomagenesis are largely unknown.The expressions of ARST in the glioma samples and cell lines were analyzed by qRT-PCR. FISH was utilized to detect the distribution of ARST in the glioma cells. CCK-8, EdU and flow cytometry were used to examine cellular viability, proliferation and apoptosis. Transwell and wound-healing assays were performed to determine the migratory and invasive abilities of the cells. Intracranial tumorigenesis models were established to explore the roles of ARST in vivo. RNA pulldown assay was used to examine proteins that bound to ARST. The activities of key enzymes in the glycolysis and production of lactate acid were measured by colorimetry. In addition, RIP, Co-IP, western blot and immunofluorescence were used to investigate the interaction and regulation between ARST, F-actin, ALDOA and cofilin.In this study, we reported that ARST was downregulated in the gliomas. Overexpression of ARST in the glioma cells significantly suppressed various cellular vital abilities such as cell growth, proliferation, migration and invasion. The tumorigenic capacity of these cells in vivo was reduced as well. We further demonstrated that the tumor suppressive effects of ARST could be mediated by a direct binding to a glycolytic enzyme aldolase A (ALDOA), which together with cofilin, keeping the polymerization and depolymerization of actin filaments in an orderly dynamic equilibrium. Upregulation of ARST interrupted the interaction between ALDOA and actin cytoskeleton, which led to a rapid cofilin-dependent loss of F-actin stress fibers.Taken together, it is concluded that ARST performs its function via a non-metabolic pathway associated with ALDOA, which otherwise modifies the morphology and invasive properties of the glioma cells. This has added new perspective to its role in tumorigenesis, thus providing potential target for glioma diagnosis, therapy, and prognosis.